Development of Land Transportation Modes as an Alternative Transportation - Ma Junyu; Ade Riusma Ariyana; Devina Arifani (IWJ : Inland Waterways Journal, 2020)
Makassar City is one of the world's cities in the Eastern Indonesia Region. As the capital city of South Sulawesi Province, it should have adequate transportation facilities and infrastructure to support the continuity of economic growth in the Eastern Indonesia Region. The density of land transportation modes is increasingly not controlled by the growth rate of vehicles. This was not supported by road construction, resulting in congestion on city roads. Seeing the polemic that has occurred in the city of Makassar regarding congestion, it is necessary to conduct a more in-depth study of the policy making implemented by the city government. Congestion in land transportation modes is one of the obstacles to the rate of economic growth in developing cities, not only in Makassar but in other cities as well. One of the solutions to overcome congestion that occurs in big cities is to develop other, more economical modes of transportation. The development of inland water transportation is one alternative to divert land transportation modes that are problematic with congestion. One of the supporting factors for the development of inland water transportation modes is when there is a traffic jam on the road.